LITERATURE REVIEW HOME PHYSICAL ENVIRONMENT, INDIVIDUAL CHARACTERISTICS, AND PERSONAL HYGIENE WITH THE INCIDENCE OF LEPROSY - Silitonga, Irene; Nurjazuli, Nurjazuli; Sulistiyani, Sulistiyani (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Leprosy is a chronic infectious disease caused by Mycobacterium leprae, which affects the skin, peripheral nerves, upper respiratory tract and eyes. According to the Ministry of Health report, in 2022 the prevalence of leprosy in Indonesia increased to 0.55 per 10,000 population. This rise in cases was influenced by various factors that contributed to the higher incidence rate across the country, Indonesia. Purpose of study: The aim of this study was to determine the association of the physical environment of the house, individual characteristics, and personal hygiene with the incidence of leprosy. Method: The method employed in this study is a literature review, with references derived from research articles published in scientific journals within the period of 2019 to 2024. Results:. As a result of the literature search, ten journals were selected based on the established inclusion criteria. While case-control designs dominated the research methodologies, a few studies employed cross-sectional approaches. The outcomes reflected certain consistencies as well as differences; nonetheless, every study documented occurrences of leprosy. Conculsion: Based on the results of the review of 10 journal articles, it can be concluded that there is a relationship between physical home environment factors, knowledge, attitudes and personal hygiene with the incidence of leprosy.